Measuring the effectiveness of credit guarantee schemes: Evidence from Malaysia - Boocock, Grahame; Mohd Shariff, Mohd Noor (SAGE Publications, 2005)
Governments across the globe are increasingly utilizing credit guarantee schemes to support SMEs.This article fills a gap in the academic literature for developing countries by reviewing the effectiveness of the New Principal Guarantee Scheme (NPGS) offered by the Credit Guarantee Corporation (CGC) in Malaysia.Using a variety of research methods, the authors investigate whether the CGC has achieved its objectives of generating finance and economic additionality without placing its financial resources under undue strain or jeopardizing its relationships with participating financial institutions.It is almost impossible to establish ‘definitive’ measures of additionality yet our findings provide sufficient evidence to demonstrate that the CGC is not meeting all of its objectives. The authors put forward an integrated package of measures designed to enhance the effectiveness of the NPGS